Skincare interventions in infants for preventing eczema and food allergy: A cochrane systematic review and individual participant data meta‐analysis. Issue 3 (25th February 2021) - Kelleher, Maeve M.; Cro, Suzie; Van Vogt, Eleanor; Cornelius, Victoria; Lodrup Carlsen, Karin C.; Ove Skjerven, Håvard; Rehbinder, Eva Maria; Lowe, Adrian; Dissanayake, Eishika; Shimojo, Naoki; Yonezawa, Kaori; Ohya, Yukihiro; et al.
Abstract: Objective: Eczema and food allergy start in infancy and have shared genetic risk factors that affect skin barrier. We aimed to evaluate whether skincare interventions can prevent eczema or food allergy. Design: A prospectively planned individual participant data meta‐analysis was carried out within a Cochrane systematic review to determine whether skincare interventions in term infants prevent eczema or food allergy. Data sources: Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase and trial registries to July 2020. Eligibility criteria for selected studies: Included studies were randomized controlled trials of infants <1 year with healthy skin comparing a skin intervention with a control, for prevention of eczema and food allergy outcomes between 1 and 3 years. Results: Of the 33 identified trials, 17 trials (5823 participants) had relevant outcome data and 10 (5154 participants) contributed to IPD meta‐analysis. Three of seven trials contributing to primary eczema analysis were at low risk of bias, and the single trial contributing to primary food allergy analysis was at high risk of bias. Interventions were mainly emollients, applied for the first 3–12 months. Skincare interventions probably do not change risk of eczema by age 1–3 years (RR 1.03, 95% CI 0.81, 1.31; I 2 =41%; moderate certainty; 3075 participants, 7 trials). Sensitivity analysis found heterogeneity was explained by increased eczema in a trial of daily bathing as part of the intervention. It is unclear whether skincare interventions increase risk of food allergy by age 1–3 years (RR 2.53, 95% CI 0.99 to 6.47; very low certainty; 996 participants, 1 trial), but they probably increase risk of local skin infections (RR 1.34, 95% CI 1.02, 1.77; I 2 =0%; moderate certainty; 2728 participants, 6 trials). Conclusion: Regular emollients during infancy probably do not prevent eczema and probably increase local skin infections.